THE SOCIAL TOURBILLON: THE REPRESENTATION OF THE MODERN CITY IN ALLEN GINSBERG'S AND ROBERTO PIVA'S POETRY - Lochini, Patricia [UNESP]; Andrade, Paulo [UNESP] (Univ Federal Santa Maria, 2019)
The quantitative disorder which characterizes the modernity, personified by the urban environment, touch the subjectivity of man who are inserted in it, and, consequently, their relationships, which suffer with the alienation of sentiments. The romantic thought of the XIX century, as a criticism to bourgeois reality, expose the empty existential of the subject that feels misfit to modern life. And, in the XX century, that spirit still illuminate the mind of the poets which keep in the search for ways to put on opposition to dehumanization of man. This way, this article have as objective reflect, by comparative analysis, how the poetry of the second half of XX century stages the sentiment of revolt, romantic par excellence, against the city as an environment of alienation, from the modernists of 50's, represented by the American beatnik poet Allen Ginsberg, to understand the modernists of 60's, represented by the Brazilian poet Roberto Piva.
Keywords: modernity; city; romanticism; resistance; modern poetry; beat generation